AUTHOR CONCEPT OF THE IMAGE OF RUSSIA IN LYON FEUCHTWANGER’S WORKS - Bril, Zhanna; Kozlovskaya, Ekaterina; Karpukhina, Nina (Revista Inclusiones, 2020)
The article proves that in the conditions of the most complicated geopolitical situation in the modern world, which entailed a confrontation between Russia and the West. On the one hand, it is continued an interest in a country with a distinctive culture and mentality unknown to foreigners; on the other hand, an analysis of Russia’s image abroad seems particularly relevant to modern science. In the author’s concept of Lion Feuchtwanger, the image of Russia is represented by the models “Russia is a happy country”, “Russia is a hospitable country”, “Russia is a lack of comfort”, “Russia is a planned structure of the state structure”, “Russia is the present / future time”, “Russia is legal state”, “Russia is education”, “Russia is the struggle / construction”, “Russia is patriotism”.